Benzodiazepine use in medical cannabis authorization adult patients from 2013 to 2021: Alberta, Canada - Cerina Dubois; Heidi Fernandes; Mu Lin; Karen J. B. Martins; Jason R. B. Dyck; Scott W. Klarenbach; Lawrence Richer; Ed Jess; John G. Hanlon; Elaine Hyshka; Dean T. Eurich (BMC, 2024)
Abstract Background Benzodiazepines are a class of medications that are being frequently prescribed in Canada but carry significant risk of harm. There has been increasing clinical interest on the potential "sparing effects" of medical cannabis as one strategy to reduce benzodiazepine use. The objective of this study as to examine the association of medical cannabis authorization with benzodiazepine usage between 2013 and 2021 in Alberta, Canada. Methods A propensity score matched cohort study with patients on regular benzodiazepine treatment authorized to use medical cannabis compared to controls who do not have authorization for medical cannabis. A total of 9690 medically authorized cannabis patients were matched to controls. To assess the effect of medical cannabis use on daily average diazepam equivalence (DDE), interrupted time series (ITS) analysis was used to assess the change in the trend of DDE in the 12 months before and 12 months after the authorization of medical cannabis. Results Over the follow-up period after medical cannabis authorization, there was no overall change in the DDE use in authorized medical cannabis patients compared to matched controls (− 0.08 DDE, 95% CI: − 0.41 to 0.24). Likewise, the sensitivity analysis showed that, among patients consuming ≤5 mg baseline DDE, there was no change immediately after medical cannabis authorization compared to controls (level change, − 0.04 DDE, 95% CI: − 0.12 to 0.03) per patient as well as in the month-to-month trend change (0.002 DDE, 95% CI: − 0.009 to 0.12) per patient was noted. Conclusions This short-term study found that medical cannabis authorization had minimal effects on benzodiazepine use. Our findings may contribute ongoing evidence for clinicians regarding the potential impact of medical cannabis to reduce benzodiazepine use. Highlights • Medical cannabis authorization had little to no effect on benzodiazepine usage among patients prescribed regular benzodiazepine treatment in Alberta, Canada. • Further clinical research is needed to investigate the potential impact of medical cannabis as an alternative to benzodiazepine medication.